MEDIA PEMBELAJARAN SPORT LITERATION BOARD UNTUK ANAK TUNARUNGU - Cahaya Permatasari, Indah; Atesya Kesumawati, Selvi; Fikri, Aprizal; Septaliza, Dewi (JURNAL ILMU KEOLAHRAGAAN, 2026)
Children with deaf in SLB face challenges in physical education due to the limited availability of learning media that are interesting, communicative, and tailored to their needs. The lack of innovative media makes the learning process monotonous. The purpose of this study was to develop Sport Literation Board-based learning media for children with deaf in grades 1–3 at SLB in Palembang City to increase their interest in learning physical education. This study employed the ADDIE method, involving 35 participants from three SLB in Palembang City. The research instrument used was a questionnaire. The results showed that the Sport Literation Board was valid with a CVR score of 0.1 (valid category). In the trial stage, children scored between 72.91 (lowest) and 100 (highest) in the small-scale trial, and between 25 (lowest) and 93.75 (highest) in the large-scale trial. These findings indicate that the Sport Literation Board is effective, practical, and suitable for adaptive physical education for children with deaf in SLB.